2015
DOI: 10.2134/agronj14.0465
|View full text |Cite
|
Sign up to set email alerts
|

Crop Rotation and Tillage Effects on Soil Physical and Chemical Properties in Illinois

Abstract: Recent increases in corn (Zea mays L.) production in the U.S. Corn Belt have necessitated the conversion of rotations to continuous corn, and an increase in the frequency of tillage. e objective of this study was to assess the e ect of rotation and tillage on soil physical and chemical properties in soils typical of Illinois. Sequences of continuous corn (CCC), 2-yr corn-soybean [Glycine max (L.) Merr.] (CS) rotation, 3-yr corn-soybean-wheat (Triticum aestivum L.) (CSW) rotation, and continuous soybean (SSS) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
90
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 45 publications
(115 reference statements)
10
90
0
2
Order By: Relevance
“…Tillage affected both SOM and TCs levels, with higher values under tilled plots as opposed to NT. Several studies have reported opposite results, showing increased SOM and TCs under longterm NT compared to tillage practices (West and Post, 2002;Kumar et al, 2012), even under Illinois conditions Zuber et al, 2015). Yet all these later studies reported results from experimental plots with more than 5 yr since treatment establishment whereas the current study has been in place for 3 yr and one complete production cycle in each field.…”
Section: Resultsmentioning
confidence: 57%
“…Tillage affected both SOM and TCs levels, with higher values under tilled plots as opposed to NT. Several studies have reported opposite results, showing increased SOM and TCs under longterm NT compared to tillage practices (West and Post, 2002;Kumar et al, 2012), even under Illinois conditions Zuber et al, 2015). Yet all these later studies reported results from experimental plots with more than 5 yr since treatment establishment whereas the current study has been in place for 3 yr and one complete production cycle in each field.…”
Section: Resultsmentioning
confidence: 57%
“…Since corn produces more residue than soybean or wheat (Triticum aestivum L.), one could assume that soil organic carbon (SOC) in a continuous corn (CC) scenario will increase more than in corn grown in a rotation. However, in a 15-year study in Illinois, Zuber et al (2015) reported similar SOC concentrations in CC and corn grown in rotation with other crops and concluded it could be attributed to lower residue production due to a yield penalty after long-term CC production and a greater overall productivity of rotations including corn. In the same study, corn-based rotations lowered bulk density (BD) and SOC compared to continuously grown soybean, which leaves low quantities of residues.…”
mentioning
confidence: 99%
“…There is mixed evidence on short-and long-term impact of crop rotations on soil properties. It is often reported that the effects of crop rotation on soil depends on the individual crop grown in a particular rotation since crops within rotation leave different quantity and quality of plant residues on the field (Sanford et al 2012;Zuber et al 2015). Leaving residues on the field has a positive effect on soils.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimum agricultural activities are considered to have the potential to restrict CO 2 emissions from soil by changing soil properties (Gregorich et al, 2005;Tenesaca and Al-Kaisi, 2015). No-tillage farming has been known to improve soil structure, reduce soil erosion, and conserve soil moisture (Gupta and Sayre, 2007;Zuber et al, 2015). Recently, no-tillage farming has received much attention because many studies have shown that it contributes to the reduction of CO 2 efflux from agricultural fields (AlvaroFuentes et al, 2007;Jabro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%